ANALISIS EFEKTIFITAS MARKA YELLOW BOX JUNCTION PADA SIMPANG TIGA AHMAD YANI KM 3 KOTA BANJARMASIN - Hardiani, Dyah Pradhitya; Ruhaidani, Emma (Jurnal Teknologi Berkelanjutan, 2023)
South Kalimantan is one of the provinces that has a large population. According to the Central Bureau of Statistics, the population of Banjarmasin City in 2023 increased by 1.51 percent. The increase in population results in a high value of road users, which has an impact on transportation problems such as congestion, one of which is the Three Ahmad Yani Km 3 Intersection. Congestion in the area is a frequent occurrence, because it is an access to the center of Banjarmasin city community activities. Efforts made by the government to control congestion are by using Yellow Box Junction markings. This study aims to determine the suitability and effectiveness of Yellow Box Junction markings. The parameters used to determine the effectiveness are the number of violators of the markings and the degree of saturation. The results showed that the intersection performance at the Ahamad Yani KM 3 Intersection in Banjarmasin City is not effective because the DS value exceeds the value specified in MKJI 1997, which is> 0.85. From the results of the percentage of violators, it is concluded that the Yellow Box Junction markings are included in the highly effective category such as in North Traffic the average value of effectiveness is 92.34%, in East Traffic the average value of effectiveness is 89.71%. The observation results of the suitability of the Yellow Box Junction markings at the Ahmad Yani KM 3 Intersection in Banjarmasin City with the applicable standards show the results are not in accordance with the size of the Yellow Box Junction markings on the width of the straight line and the width of the diagonal line of 30 cm.